Stigmatisasi terhadap Tiga Jenis Seni Pertunjukan di Banyuwangi: dari Kreativitas Budaya ke Politik - Hervina Nurullita (Jurnal Kajian Seni, 2016)
This research aims to fi nd out how stigmatization toward Banyuwangi people throughthree performing arts: Damarwulan, Gandrung and Banyuwangi local music. At thefi rst emergence of three performing arts come from cultural creativity has backgroundof each. In their developments, these three performing arts genres becomes even morepopularized, for not only Banyuwangi people but also Javanese people especially EastJava and Middle Java. This popularization happened along with social, cultural andpolitical change in Java, especially Banyuwangi. Along with this, all of this social,cultural and political change becomes stigmatized towards the three performing artsin Banyuwangi. This stigmatization is related to social reality and political events inBanyuwangi especially in the postcolonial era.This research concludes that there is no purpose from artists to create a stigmatizationtoward three performing arts in Banyuwangi; Damarwulan, Gandrung and Banyuwangilocal music. There is no evidence of giving stigmatization when the artists produce thespecifi c art forms. This stigmatization happens along with social, cultural, political changein the history of Banyuwangi.